IMPLEMENTASI SERAH SIMPAN KARYA CETAK DAN KARYA REKAMAN DI LINGKUNGAN PERGURUAN TINGGI - Venantia Sri Hadiarianti (Jurnal Paradigma Hukum Pembangunan, 2019)
Basically the manifestation of creativity, sensitivity, and activity is protected by copyright. In the context of higher learning institution each professor has a main obligation to implement the three works of higher learning institution (Tri Dharma Perguruan Tinggi). The substance of the three works is full with the content of copyright, especially research work. The result of a research which is still in the form of manuscript can be submitted to the university library if it does not need publication. And what is publicized to be a book according to the Law Number 4 Year 1990 about the Submission of Printed Works and Recorded Works has to be submitted to and saved in National Library (two books) and Regional Library (one book) by the publisher or an institution legalized in the Government Regulation. In 2014 was issued the Law Number 28 Year 2014 about Copyright. By using the normative juridical research method some issues are to be scrutinized. Firstly, relation between the Law Number 4 Year 1990 about the Submission of Printed Work and Recorded Work and the Law Number 28 Year 2014 about Copyright. Secondly, the implementation of the Law Number 4 Year 1990 about the Submission of Printed Works and Recorded Works in the context of higher learning institution. It is found that both of the Laws are related to eachother in regard with the printed works and recorded works as the object of copyright. The Law Number 4 Year 1990 has not been effective yet according to the mandate of the law.